THE CURRENT STATE OF FISH PRODUCTION IN THE REPUBLIC OF UZBEKISTAN AND THE ROLE OF TASHKENT REGION - Umurzokov Shakhzodbek (Modern American Journals, 2025)
This article provides an in-depth analysis of the current state of fish production in the Republic of Uzbekistan, highlighting its territorial characteristics as well as the geographical and economic foundations of the sector. Fish farming is considered a strategically important industry in ensuring food security, improving public health, and enhancing the country’s export potential. As such, it has become one of the priority areas of state policy.The article analyzes, based on statistical data, the water resources of Tashkent Region, the availability of natural and artificial water bodies, and the achievements resulting from the implementation of intensive fish farming technologies. By the end of 2024, Tashkent Region had produced 27.1 thousand tons of fish, making it the second-largest contributor to the country’s total fish production. Furthermore, the paper examines the spatial distribution of fish farms, their infrastructural development, proximity to domestic markets, and advantages in terms of export potential.
Keywords: Fish farming, statistical data, fish catch, Tashkent Region, agriculture, intensive aquaculture.